Proceedings of the 20th ACM International Conference on Intelligent Virtual Agents 2020
DOI: 10.1145/3383652.3423869
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use Screening using Virtual Agents

Abstract: Alcohol, tobacco and illicit drug use cause significant loss quality of life, and represent a large economic burden on society. Standardized questionnaires have been developed to enable healthcare providers to screen individuals for substance misuse problems that may require intervention. Although routine use of these screeners is promoted in many healthcare organizations, their administration can be irregular and lack follow through. In addition, patients may be reluctant to report substance use. We report on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…One example of this can be seen in a recent randomized controlled trial (RCT) that demonstrated higher quality motivational interviewing skills in a real-world setting with clinicians who practiced with a VP following a U.S. Department of Veterans Affairs (VA) online training course compared with those who took the VA course plus time-equivalent (to VP practice) refresher training (Reger et al, 2020). VHs have also been created to produce online and mobile health care guides (Bickmore et al, 2020;Mozgai et al, 2020Mozgai et al, , 2021Rizzo et al, 2015) as clinical interviewers (Philip et al, 2017), sometimes with automated sensing of facial, gestural, and vocal behaviors useful for inferring the state of the user interacting with these VH entities (Rizzo et al, 2016) and for assessing empathetic behavior with clinical trainees (Yao et al, 2020). Recently, innovative efforts have appeared using embodied "body ownership" VH activities for addressing intimate partner violence (Gonzalez-Liencres et al, 2020;Matamala-Gomez et al, 2021), teaching self-compassion in persons with depression (Cebolla et al, 2019;Falconer et al, 2016), and promoting empathy in users who experience the challenges of another person via a virtual experience (Herrera et al, 2018).…”
Section: Engagementioning
confidence: 99%
“…One example of this can be seen in a recent randomized controlled trial (RCT) that demonstrated higher quality motivational interviewing skills in a real-world setting with clinicians who practiced with a VP following a U.S. Department of Veterans Affairs (VA) online training course compared with those who took the VA course plus time-equivalent (to VP practice) refresher training (Reger et al, 2020). VHs have also been created to produce online and mobile health care guides (Bickmore et al, 2020;Mozgai et al, 2020Mozgai et al, , 2021Rizzo et al, 2015) as clinical interviewers (Philip et al, 2017), sometimes with automated sensing of facial, gestural, and vocal behaviors useful for inferring the state of the user interacting with these VH entities (Rizzo et al, 2016) and for assessing empathetic behavior with clinical trainees (Yao et al, 2020). Recently, innovative efforts have appeared using embodied "body ownership" VH activities for addressing intimate partner violence (Gonzalez-Liencres et al, 2020;Matamala-Gomez et al, 2021), teaching self-compassion in persons with depression (Cebolla et al, 2019;Falconer et al, 2016), and promoting empathy in users who experience the challenges of another person via a virtual experience (Herrera et al, 2018).…”
Section: Engagementioning
confidence: 99%
“…Moreover, they have been used to provide personalized interventions depending on patient data (46). Relational agent applications have spanned a wide variety of health care areas, including palliative care (48), preconception care (49), atrial fibrillation (50), cancer genetics (51), chronic illness (52), health behavior change (47), and psychiatry (53). Relational agents most commonly act as counselors but also as interviewers for health data or screens (50,51,54,55), health coaches (47), patient advocates and educators (49), and patient companions (56).…”
Section: Evidence Of Effectsmentioning
confidence: 99%
“…Prior work has demonstrated the effectiveness of ECAs in delivering health promotion interventions and effectively using health counseling techniques (e.g., Cognitive behavior therapy, Motivational Interviewing, etc.) to facilitate behavior change on a myriad of health topics, including but not limited to physical activity (King et al, 2020), genetic counseling (Zhou & Bickmore, 2022), preconception care (Jack et al, 2020), substance use (T. Bickmore et al, 2020b), and depression (Laranjo et al, 2018;Ring et al, 2016a). ECAs have been shown to successfully develop a positive therapeutic working alliance with users presenting a somewhat straightforward translation from in-person screening and counseling to a digital intervention (T. Bickmore & O'Leary, 2023).…”
Section: Embodied Conversational Agents In Mental Healthcarementioning
confidence: 99%
“…Bickmore et al designed a tablet-based alcohol misuse screening ECA. They evaluated the system in two counterbalanced mixed methods validation studies with 57 participants, comparing the ECA to a human and an existing forms-based assessment (T. Bickmore et al, 2020a). Both studies demonstrated the validity of the ECA as a screening tool.…”
Section: Screeningmentioning
confidence: 99%
See 1 more Smart Citation